DEVELOPMENT OF THE «RISKS - OPPORTUNITIES* MATRIX FOR ASSESSING STRATEGIC RISKS AND OPPORTUNITIES OF THE CHEMICAL INDUSTRY - N. Solovyova (Вестник Северо-Кавказского федерального университета, 2022)
The article proposes and tests the «risk-opportunity» matrix for the purpose of assessing the strategic risks and opportunities of chemical companies as dichotomous categories reflecting the probabilistic nature of the environment for the functioning of objects. The author has developed an approach to determining the position of a company in the matrix based on a system offactors differentiated for a number of reasons depending on the goals, subjects and objects of assessment. The system of factors included both general economic and industry-specific factors, the significance of which is determined by the author using the importance coefficients.